IPTEKS PENYUSUNAN ATAU PEMUTAKHIRAN DATA PROFIL WAJIB PAJAK OLEH ACCOUNT REPRESENTATIVE DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Sinjal, Ave Ceriti; Mintalangi, Syermi S. E (Universitas Sam Ratulangi, 2018)
Account Representatives in KPP Pratama Manado have task to construct and update data profile of taxpayers. Valid source of data is a must for Account Representatives to do their task. By using internal datas from DJP such as SIDJP, MPN, Master File, Portal Intranet DJP or datas in Tax Amnesty are choices for Account Representatives in KPP Pratama Manado to run it, besides there are some way that can be used like digital technologies or do visit directly to taxpayers. The purpose of this study is to know the way Account Representative in KPP Pratama Manado using data sources given by DJP or KPP Pratama itself, digital technologies or visiting taxpayers in order to construct or update data profile of taxpayers. Suggestion for KPP Pratama Manado is to updates the use of data sources owned by DJP’s internal system and to maximizing digital technologies, such as telephone and electronic chatting application directly to taxpayers to help AR do their tasks effectively and efficiently.Keywords : taxpayer, profile, account representative, data source